Assessment of meridic larval and adult diets for mass rearing of Bactrocera dorsalis (Diptera: Tephritidae) - Mahfuza Momen; Md. Shahjalal; Md. Ashikur Rahman; Md. Aftab Hossain; Md. Kamruzzaman Munshi; Kajla Seheli (PLoS ONE, 2025)
The oriental fruit fly, Bactrocera dorsalis (Diptera: Tephritidae), is a widespread pest in Bangladesh. Sterile Insect Technique (SIT) offers a solution for effectively suppressing this fruit fly species. However, SIT involves mass rearing of fruit fly species in a laboratory where a standardized artificial rearing diet is crucial for ensuring uniform growth, development, and reproduction. In this study, we assessed efficacy of a new formulated gel-based meridic larval diet as well as protein and carbohydrate rich adult diets for the rearing of B. dorsalis in laboratory conditions. Proximate analysis was conducted for our formulated rearing diets to determine the content of moisture, protein, fat, carbohydrate, and ash. For our formulated diets, several key biological parameters, including egg hatching rate, pupation rate, pupal weight, adult emergence, adult growth, sex ratio, and flight capacity, were assessed. Statistical analysis using Tukey box plots revealed a significant improvement for the laboratory reared body parameters of adults while maintained in meridic diets, as compared to their wild counterparts. Adults fruit flies reared on our formulated meridic adult diets exhibited sufficient longevity, especially when compared to those provided with only water. In addition, our study presents survival analysis using non-parametric Kaplan–Meier estimator and Weibull parametric model. Our findings indicate that the formulated diets presented in this study can be effectively incorporated into B. dorsalis laboratory mass-rearing, meeting the required standard quality parameters outlined in the FAO/IAEA/USDA mass-rearing guideline of tephritid fruit flies.